Mammary gland cancer, endobronchial mestastasis: Diagnostic and therapeutic considerations - Viola Alles, Alberto; Etchebarne, Liliana; Sabini, Graciela; Pacheco, Héctor (Cirugía del Uruguay, 1984)
Authors point out the difficulty of making a differential diagnosis between endobronchial metastasis of mammary gland carcinomas and the bronchopulmonary primary tumours, that is, a second tumour in a patient suffering mammary gland cancer.